(3TQM CHjGJ GdLeds - (3eMeO Hf CMeO Hf gTGe Hf Nda GddNej GdCfOdSj, CHh YHO Gddg,J (B577 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdEfSGf hYdeg GdHjGf ? bGd GdeDda hfMf fHOC HPcQ fHPei GdCHjGJ GdJi dG JTJZd HCfaSgG ef WQjb GdEYQGH hGdeYfj s
(3BNQgG (B:s
(3hbGd YeQ Hf YHO GdYRjR ef de ef Yde cKQJ NWGjGg Je GdcJGH HMeO Gddg s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B318 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B26 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B97s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3eJaQbGJs